The World Book Encyclopedia of People and Places - World Book, Inc. (Chicago World Book, 2002)
Encyclopedia, dictionary and geography of people and places
Include Color Illustration and Map
Afghanistan to Czech Republic
Keywords: Encyclopedias and dictionaries -- Geography -- Geography -- Encyclopedias